CUSSING AMONG THE KANKANAEY YOUTH - Domingo, Ephraim; Caroy, Analyn; Carambas, Janice; Dizon, Elaine Grace; Po-or, Karyl (Cadernos de Linguagem e Sociedade, 2019)
This paper explores the cuss words used by the Kankanaey young people of The Philippines, examines the reasons they use them and if these cuss words reflect their identity. It employs the qualitative approach and uses a semi-structured interview. Most of the cuss words are terms that range from taboo topics such as the genitals, to inoffensive terms such as body parts, to incapacity, and to words borrowed and modified from English, as well as those invented. These cuss words are usually used to express emotions that range from light to strong ones such as anger, disappointment, fright, or surprise.